Contemporary Slavic word-derivation theories: An overview of the work from Polish linguistics - Koriakowcewa Elena I. (Južnoslovenski Filolog, 2015)
This paper describes the main research tendencies of the word-derivation theory in the Polish linguistics at the turn of 21st century. The synchronic and diachronic methods which are used in the analyses of derivative nests, categories and types of the Polish language are described. The article presents a short overview of the research produced by the Polish word-derivation linguists and historians of language who belong to Silesian linguistic school of thought, which deals with the “perspective evolution” of the derivational categories as applied to the parts of the speech. There is also a general overview of the Silesian approach to problems of historical derivation that is described as a system formed under the influence of various extralingustics and intraligustics evolution factors.